Recommendations For Improving Exclusive Breast Milk For Working Mothers With Health Action Process Approach (Hapa) In Batu Bara District - Elza Fahliza Ismar; Herisa Putri Anggraini; Ermi Girsang; Ali Napiah Nasution; Putranto Manalu (International Journal of Health and Pharmaceutical (IJHP), 2022)
Mother's Milk (ASI) is the main and best food for babies that have no equal. The benefits of exclusive breastfeeding are enormous, especially for the baby's growth and development, immunity, psychology, and the economy of the baby's parents. Even though the benefits of exclusive breastfeeding are clear for mothers and their babies, the coverage of exclusive breastfeeding for babies is still low. The purpose of this study was to analyze the increase in exclusive breastfeeding for working mothers using the Health Action Process Approach (HAPA) in Batu Bara Regency. The sample of this research is working mothers who have babies 0-6 months in Batu Bara Regency. The sampling technique is Non-Probability Sampling using Total Sampling, where the number of samples is the same as the population of 100 people. The data processing method used Univariate, Bivariate, and Multivariate tests. Theresults showed that self-efficacy, outcome expectations, risk perception, planning, the effect of intention, maintenance, and planning strategies to overcome barriers had a significant effect on breastfeeding practices for working mothers in Batu Bara Regency as evidenced by the p-value of each variable 0.000 <0.05. The multivariate test results show that together the independent variables have a significant effect on the dependent variable, with the most dominant variable being the maintenance variable with an average value of 10.66. The frequency of exclusive breastfeeding and the duration of breastfeeding has no effect on the practice of breastfeeding for working mothers in Batu Bara Regency.